2008
DOI: 10.1021/cm8007478
|View full text |Cite
|
Sign up to set email alerts
|

Silica Nanoparticles with Continuously Tunable Sizes: Synthesis and Size Effects on Cellular Contrast Imaging

Abstract: Controlling the size of silica nanoparticles (NPs) on a continuously variable scale was achieved by systematically varying the organic solvent(s) used in water-in-oil microemulsion synthesis. A number of individual as well as binary solvent mixtures were investigated for tuning silica NP size. The results demonstrated that the size of a silica NP was continuously tunable over as range of 20-100 nm by varying the alkane chain length of the organic solvent(s) being used. A simple physical model was proposed to d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
106
0
1

Year Published

2009
2009
2018
2018

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 101 publications
(109 citation statements)
references
References 39 publications
2
106
0
1
Order By: Relevance
“…This synthetic process takes more time than the Stöber method. However, the reverse microemulsion method can overcome the limitations of the Stöber method [25,[55][56][57] by producing silica nanoparticles with a uniform size distribution. Furthermore, this method can efficiently dope dye molecules into the silica nanoparticles.…”
Section: Reverse Microemulsion Methodsmentioning
confidence: 99%
“…This synthetic process takes more time than the Stöber method. However, the reverse microemulsion method can overcome the limitations of the Stöber method [25,[55][56][57] by producing silica nanoparticles with a uniform size distribution. Furthermore, this method can efficiently dope dye molecules into the silica nanoparticles.…”
Section: Reverse Microemulsion Methodsmentioning
confidence: 99%
“…Jin and co-workers studied the effect of size on the penetrating ability of NPs fabricated by ME and they showed that the small NPs (23 ± 3 nm) clearly penetrated the cells much faster than larger NPs (85 ± 5 nm). [ 41 ] In addition, the better image quality achieved with NPs-LA is assigned to their larger values of σ TPA (see Figure 6 ).…”
Section: Organic Fluorescent Nanoparticles For Bioimaging Applicationsmentioning
confidence: 97%
“…Size distribution Medium [27,28] Wide [32,38] Narrow [34] Tunable size Easy a) [15,36] Easy [39] Easy [40,41] Stability Stable fl uorescence a) [42] Stable fl uorescence [33] Stable fl uorescence [43,44] Aggregation Low [15,28,45] Low-medium [46] Medium [47][48][49] Surfactant Not necessary a) [50,51] Not necessary [31,52] Removed after purifi cation…”
Section: Structurementioning
confidence: 99%
“…nanowires [9], nanotubes [10,11] and nanorods [12]) as well as 3D silica nanostructures (e.g. nanoparticles [13,14] and nanocubes [15]) have been widely investigated. Recently, graphene-supported large area silica nanosheets have been reported by our group [16].…”
mentioning
confidence: 99%